Designing emergency support functions for functional exercise. A case study in field of firefighting in Haiphong, Vietnam - Thang T N; Khuong N M; KATO T (International Conference on Engineering and Technology Development (ICETD), 2017)
Hazard and risk of accidents exist all over the world as part of human life. From developed countries as United State of America and Japan to developing countries as Indonesia and Vietnam; governments, organizations and communities share their specific responsibility in emergency management depending on history of disasters, policy structures and cultures. Emergency training and exercise are important programs to enhance the resilience of society. The Deming cycle known as Plan-Do-Check-Act (PDCA) cycle is effective instrument for continuous improvement of management. Therefore, doing preparedness exercises play a significant role of emergency plan improvement. Our research focuses on how to evaluate adequacy of emergency plans and resources of organizations through table-top and functional exercises. In particular, we research on designing effective exercises for emergency relief organizations. Through reviewing different styles of functional exercise, we introduce and verify idea of Kitakyushu functional exercise (KFEX) in Vietnam. KEFX is a new style of doing functional exercise by providing methods of exercise design, data observation and results analysis. It provides possibility to evaluate quantitatively trainee performances through timing each task of participants and utilizing a cloud support-software tool for functional exercise. To apply KEFX in context of Vietnam, we designed a functional exercise in considering the structure of emergency relief organizations. Haiphong Police of fire prevention and fighting (Haiphong PoFF) has been defined as a case study to expand KFEX idea. Because emergency support functions (ESFs) are foundation to design exercise, we proposed and checked ESFs for functional exercise in Haiphong city, Vietnam. In March 2017, we implemented the demonstration of function exercise as a feasible study for applying idea of KFEX. Participants in the demonstration include Controller group, Evaluator group and Player group, those belonged to Haiphong PoFF. Task processing network and time consumption for each task were recorded by software support tool. In this paper, we will explain process of exercise design and share results after the demonstration in Haiphong PoFF.